7(9+x)=147

Simple and best practice solution for 7(9+x)=147 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(9+x)=147 equation:


Simplifying
7(9 + x) = 147
(9 * 7 + x * 7) = 147
(63 + 7x) = 147

Solving
63 + 7x = 147

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-63' to each side of the equation.
63 + -63 + 7x = 147 + -63

Combine like terms: 63 + -63 = 0
0 + 7x = 147 + -63
7x = 147 + -63

Combine like terms: 147 + -63 = 84
7x = 84

Divide each side by '7'.
x = 12

Simplifying
x = 12

See similar equations:

| 5-8b+6-2b= | | 15x+40=8x-9 | | -33=-x+7x-3 | | h=6t^2+112t+1248 | | -2y^2+16y-x-28=0 | | -2(8t^2-48t-8)=0 | | X^3+4x=80 | | 47.75=5(2.95+x) | | 3(2x+5)-x=-5x-15 | | 3x=27.9 | | 4a^2-7a-2=0 | | x+(4x)=5 | | (2t^2-t-15)/(3t^2-8t-3) | | 3(2x+5)-x=4x+15 | | 6m^2=13m+38 | | =5+7(0)+4 | | ln(x)=1/9 | | y=-4/3x^2-8x | | -3x-23=3x+19 | | 7-4x-6x=-3 | | 2x+(1-x)=7 | | x+(x+1.3)+(x-1.3)=27.9 | | 3(2x+5)-x=15x+5 | | 225=50t | | x-1(x+7)=500 | | 1+4=2+3 | | 6m^2-5m-6=0 | | 3(2x+5)-x=-5x+10 | | y=-3x-23 | | 12-4=3+6 | | 2q+397=813 | | 3(2x+5)-x=-4x+15 |

Equations solver categories